Radiopharmaceuticals Adverse Events Management - Martínez, Ana Agudo; Hernández, Gertrudis Sabatel; Mora, Manuela Molina; la Riva Pérez, Pablo Antonio de; López, Rosa Fernández; Molina, Teresa Cambil; Morón, Cinta Calvo (Current Radiopharmaceuticals, 2025)
Background and Purpose Radiopharmaceuticals are radioactive compounds used for diagnostic or therapeutic purposes which are most often administered intravenously. Adverse events that may induce both adverse reactions and drug-to-drug interactions with changes in expected biodistribution, potentially affecting patient safety and diagnostic accuracy. Adverse reactions are relatively rare due to the small doses and under-reporting is the norm. The aim of this study is to increase awareness of the need to report in order to create protocols for the management of such adverse events among professionals in a Nuclear Medicine Department. Methods A reporting system was established a decade ago through an electronic form to enhance adverse event registration. The radiopharmacist collects data for further communication with National Health authorities and develops an annual report with recommendations on the management of these adverse events. Results A total of 128 reports were collected, including 65 cases of extravasations, 18 adverse reactions, and 45 drug interactions. Over the years, reporting has been increasing, adverse reactions occurred at a higher incidence than reported in the literature, and each anomalous biodistribution was analysed for possible drug interaction. The annual reports have been used to develop a local guideline for the management of adverse reactions and recommendations for discontinuation of treatment to avoid interactions with radiopharmaceuticals. Conclusion The recognition of adverse events associated with radiopharmaceuticals is increasing, underlining the need for vigilant reporting and improved management strategies. An efficient reporting system promotes awareness of possible interactions between radiopharmaceuticals and other medicines and their potential adverse reactions to enhance patient safety.
Keywords: diagnostic accuracy